Forage Grasses Steer Soil Nitrogen Processes, Microbial Populations, and Microbiome Composition in A Long-term Tropical Agriculture System - Momesso, Letusa [UNESP]; Crusciol, Carlos A.C. [UNESP]; Leite, Marcio F.A.; Bossolani, Joao W. [UNESP]; Kuramae, Eiko E. (Elsevier, 2022)
Forage grasses used in cropping no-till systems in tropical regions alter soil chemical properties, but their long-term impact on soil microbial processes of the nitrogen (N) cycle and microbial community abundance, composition and structure are unknown. Here, microbial functions related to nitrogen fixation, nitrification and denitrification as well as bacterial, archaeal and fungal populations were evaluated in a long-term field experiment in which tropical forage grasses palisade grass (Urochloa brizantha (Hochst. Ex A. Rich.) R.D. Webster) and ruzigrass (U. ruziziensis (R. Germ. and C.M. Evrard) Crins) were cultivated with or without N fertilization. Uncultivated soil was used as a control. Forage grasses, especially palisade grass, increased soil bacterial and fungal abundances, whereas the archaeal population was highest in uncultivated soil. In soils cultivated with forage grasses, N fertilization favored N-cycle-related genes; however, cultivation of palisade grass increased the abundances of amoA bacteria (AOB) and amoA archaea (AOA) genes associated with soil nitrification and decreased the abundances of genes nirS, nirK and nosZ genes related to denitrification, compared to ruzigrass and control, regardless of N input. In addition, abundances of total bacteria and total fungi were associated with the N cycle and plant biomass in soils cultivated with forage grasses. Forage cultivation clearly benefitted the soil nutrient environment (S-SO42-, Mg2+, total-C and -N, N-NO3- and N-NH4+) and microbiome (bacteria and fungi) compared with uncultivated soil. In soil cultivated with palisade grass, the microbial community composition was unresponsive to N addition. The high N uptake by palisade grass supports the competitive advantage of this plant species over microorganisms for N sources. Our results suggest that palisade grass has advantages over ruzigrass for use in agriculture systems, regardless of N input.
Keywords: Bacteria; Brachiaria spp.; Fungi; N cycle; Nitrogen fertilizer; No tillage system